Anion⋅⋅⋅Anion Attraction in Complexes of MCl3− (M=Zn, Cd, Hg) with CN−. Issue 11 (5th May 2020) - Wysokiński, Rafał; Zierkiewicz, Wiktor; Michalczyk, Mariusz; Scheiner, Steve
Abstract: High‐level ab initio calculations show that the MCl3 − anions comprising Group 2B M atoms Zn, Cd, and Hg form a stable complex with the CN − anion, despite the like charge of the two ions. The complexation occurs despite a negative π‐hole region above the M atom of MCl3 − . The dimerization distorts the planar geometry of MCl3 − into a pyramidal shape which reduces the negative potential above the M atom, facilitating a close approach of the two anions, with R(M⋅⋅⋅C)∼2 Å, and an overall attractive electrostatic attraction within the dimer. In the gas phase, this dimer is less stable than the pair of separated ions by some 30 kcal/mol. However, the dissociation must surmount an energy barrier of roughly 25 kcal/mol which occurs at an intermolecular distance of 4 Å. In aqueous solution, the dimerization process is exothermic and barrier‐free, with a binding energy in the 11–18 kcal/mol range. Abstract : Complexation between two anions CN − and MCl3 − (M=Zn, Cd, Hg) occurs despite a negative π‐hole region above the M atom of MCl3 − .